11 The identification of subclinical enteric protein loss in children with univentricular circulation following total cavopulmonary connexion. (2nd February 2018) - Breatnach, CR; Cleary, A; Prendiville, T; Crumlish, K; Murchan, H; McMahon, CJ
Abstract : Purpose: Protein Losing Enteropathy post Fontan palliation is associated with significant morbidity and mortality. To date, very little research has been carried out to improve early identification of enteric protein loss in these patients. We hypothesise that subclinical enteric protein loss may occur in patients post Fontan surgery. Methods: A cross sectional study was performed on 43 patients post Fontan surgery. We collected specimens of stool and blood from well patients, with no symptoms of protein losing enteropathy post Fontan. Stool samples were assessed for alpha one antitrypsin. The stool samples of two patients were discarded, leaving 41 stool samples. Blood samples were also collected to review albumin, C-reactive protein, liver and renal function. Results: Twenty eight (65 percent) of those enrolled were male. The median (IQR) age between Fontan and collection of study specimens was 3.5 (2–7) years. Two (5 percent) patients had elevated levels of alpha-1-antitrypsin. There was no correlation between blood biochemistry and elevated stool alpha-1-antitrypsin. Conclusion: Subclinical protein loss is rare in asymptomatic children after Fontan procedure with only 5 percent of patients having elevated stool alpha-1-antitrypsin but no other symptoms. These findings may relate to our small cohort size and the time to testing post cardiac surgery. Future longitudinal follow up studies should assess the ability of alpha-1-antitrypsin to provide earlier detection of protein losing enteropathy in asymptomatic patients post Fontan. Given the serious prognosis of protein losing enteropathy in this patient group further work is warranted.